Tumor immune escape in acute myeloid leukemia: Class II-associated invariant chain peptide expression as result of deficient antigen presentation - van Luijn, Marvin M. (Landes Bioscience, 2012)
In this overview, we discuss the role of class II-associated invariant chain peptide (CLIP) in acute myeloid leukemia (AML), one of the few tumors expressing HLA class II. The clinical impact, function and regulation of CLIP expression on leukemic cells is addressed, indicating its potential as immunotherapeutic target in AML.